Web Based VCD/DVD Ordering System - A Prototype - Chong, Lai Lai (2003)
Web based ordering have become an interesting e-commerce technique within the brick-and-mortar stores. Therefore, this project mainly aims to develop a start up version of a Web Based VCD/DVD Ordering System for a case organization namely Golden Star VCD Store that on the whole sells the VCD/DVD movie products. However, as the time and budget constraint, the project focused on build up a prototype Web Based VCD/DVD Ordering System for the store. As the Internet accessibility has shown a growing numbers in Malaysian home, therefore this project hope to provide an alternative way of gaining competitive advantages for Golden Star VCD Store throughout the country despite enable the customers to experience a new way of purchasing the VCD/DVD. The methodology used for this project is derived from Rational Unified Process (RUP) that has been customized by applying Unified Modeling Language (UML) technique to analyze and design the prototype system. As a result, this prototype is the start up version for Web Based VCD/DVD Ordering System provides customers the ability to view the products and check for the products availability with the facility to preview the movie trailer on the web, specify the account information, add the preference products to the shopping cart or order list, and finally login for check out to place the order. This study is significance to provide a reference model for the brick-and-mortar store to start up the web based ordering application using MySQL and PHP open source. Thus, this study provides an alternative way for the customers to purchase the products through the web based application in spite of the brick-and-mortar stores with more convenience service. This report presents the evaluation of the prototype system based on usability testing to evaluate users’ satisfaction and concludes with the recommendations for enhancement of the prototype and future research of the system.